A review on chitosan and chitosan-based bionanocomposites: Promising material for combatting global issues and its applications - Azmana, Motia; Syed, Mahmood; Hillese, Ayah Rebhi; Rahman, Azizur; Mohd Azmir, Arifin; Ahmed, Shakeeb (Elsevier Ltd, 2021)
Over the last few years, several attempts have been made to replace petrochemical products with renewable and biodegradable components. The most challenging part of this approach is to obtain bio-based materials with properties and functions equivalent to those of synthetic products. Various naturally occurring polymers such as starch, collagen, alginate, cellulose, and chitin represent attractive candidates as they could reduce dependence on synthetic products and consequently positively impact the environment. Chitosan is also a unique bio-based polymer with excellent intrinsic properties. It is known for its anti-bacterial and film-forming properties, has high mechanical strength and good thermal stability. Nanotechnology has also applied chitosan-based materials in its most recent achievements. Therefore, numerous chitosan-based bionanocomposites with improved physical and chemical characteristics have been developed in an eco-friendly and cost-effective approach. This review discusses various sources of chitosan, its properties and methods of modification. Also, this work focuses on diverse preparation techniques of chitosan-based bionanocomposites and their emerging application in various sectors. Additionally, this review sheds light on future research scope with some drawbacks and challenges to motivate the researchers for future outstanding research works.